1980
DOI: 10.1007/bf00441583
|View full text |Cite
|
Sign up to set email alerts
|

Success, relapse and failure after intranasal LHRH treatment of cryptorchidism in 55 prepubertal boys

Abstract: Synthetic LHRH was given intranasally to 55 prepubertal boys with 67 undescended testes. After a 4-5 week period while receiving a daily dose of 1.2 mg complete testicular descent was seen in 24 testes. Follow-up over 6 to 24 months showed relapse in 4 boys who responded successfully to a second trial with LHRH. In boys with insufficient or no response to an initial trial further treatment with LHRH in 11 cases or HCG in 5 cases also was without effect. Surgical correction after unsuccessful LHRH treatment in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
1

Year Published

1982
1982
2001
2001

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(5 citation statements)
references
References 8 publications
0
4
1
Order By: Relevance
“…In this collaborative study involving a large number of 119 cryptorchid patients who were prospectively treated and followed up, the overall success rate of complete testicular 80% (15). This is in contrast to the findings of Illig et al who reported that hCG treatment given to four boys unresponsive to LHRH treatment had no effect on testicular position (13). The same authors stated that a second trial of intranasal LHRH in 17 boys with no or insufficient response to the initial LHRH treatment was ineffective, regardless whether it followed immediately after the first course or whether it was repeated weeks or months later.…”
Section: Discussioncontrasting
confidence: 58%
See 1 more Smart Citation
“…In this collaborative study involving a large number of 119 cryptorchid patients who were prospectively treated and followed up, the overall success rate of complete testicular 80% (15). This is in contrast to the findings of Illig et al who reported that hCG treatment given to four boys unresponsive to LHRH treatment had no effect on testicular position (13). The same authors stated that a second trial of intranasal LHRH in 17 boys with no or insufficient response to the initial LHRH treatment was ineffective, regardless whether it followed immediately after the first course or whether it was repeated weeks or months later.…”
Section: Discussioncontrasting
confidence: 58%
“…Two studies were conducted double-blind and included 84 and 100 patients, respectively (10, 16). This is in contrast to the findings of Illig et al who reported that hCG treatment given to four boys unresponsive to LHRH treatment had no effect on testicular position (13). Success rates in therapeutic trials with this drug have generally varied between 3 0 4 0 % (9-16) and could not be increased by treatment periods of more than four weeks (9-1 1, 13).…”
Section: Discussionmentioning
confidence: 88%
“…Nasal application of LH-RH has been shown to give therapeutic effect in about 30-60% of patients with undescended testes (Illig et al 1977(Illig et al , 1980Pirazolli et al 1978;Had~iselimovia 1982). In both these studies comprising 96 treated patients with a total of 116 undescended testes a therapeutic result was found in about 60% and a complete descent was found in about 40%.…”
Section: Discussionmentioning
confidence: 98%
“…injections for 14 days. When synthetic LH-RH preparations for intranasal application were available, several studies on treatment of undescended testes have been presented (Happ et al 1975(Happ et al , 1978Illig et al 1977Illig et al , 1980Pirazolli et al 1978). Success rate varies between 30 and 60%.…”
Section: Introductionmentioning
confidence: 97%
“…Many patients receiving the 6 week stimulation, had hormonal levels obtained at 6 weeks but also after 6 days, and 3 weeks. Assay procedures for LH, FSH,9 and testosteronel° were carried out as previously reported.…”
Section: Methodsmentioning
confidence: 97%